The Effects of Using Clove Meal (Syzygium aromaticum L.) as Feed Additive on Nutrient Digestibility and Metabolizable Energy of Broiler Chicken - Irfan H Djunaidi; Siti Azizah; Mohamed Shakal (Jurnal Ilmu-Ilmu Peternakan, 2023)
This study was aimed at determining the effect of clove meal addition in diets on nutrient digestibility and metabolizable energy in broilers and whether it could be an alternative to antibiotics or not. In this experiment, twenty-four 35-day-old broilers of the chicken strain Lohman were used. A total of twenty broiler chickens were selected as representatives for determining the digestibility. The treatment diets were: T0 (basal diet), T1 (basal diet + 0.25% clove meal), T2 (basal diet + 0.5% clove meal), T3 (basal diet + 0.75% clove meal), and T4 (basal diet + 1% clove meal). The variables measured were dry matter digestibility, organic matter digestibility, apparent protein digestibility, true digestible protein (TDP), Apparent Metabolizable Energy (AME), True Metabolizable Energy (TME), Nitrogen Corrected Apparent Metabolizable Energy (AMEn) and Nitrogen Corrected True Metabolizable Energy (TMEn). A completely random design was used, with five treatments and four replications. The data were analyzed using analysis of variance (ANOVA), and differences among treatments were examined using Duncan’s multiple range test. The results show that the treatment influences significantly (P<0.05) of dry matter, organic matter, apparent protein digestibility, and TDP. In contrast, there were no significant effects (p>0,05) of dietary treatment on AME, TME, AMEn, and TMEn. However, the addition of 0.75% clove meal indicated the best result in AME, TME, AMEn, and TMEn. It can be concluded that the experiment indicated that the addition of clove meal (Syzygium aromaticum L.) in 0.75% on the diet of broiler chickens was effective in increasing the digestibility of dry matter, organic matter, crude protein, TDP, and metabolizable energy.